Journalism, media & technology: the challenges! / Faridah Hanem Ab Rashid …[et al.]. - Ab Rashid, Faridah Hanem; Amanah, Farah Hazween; Khairul Anuar, Nurliyana Kamilah; Ramlan, Muhammad Azril Izuan; Hassan @ Assan, Amirah (Universiti Teknologi MARA, Negeri Sembilan, 2024)
The advent of digital technology has revolutionised the way news is disseminated, allowing for rapid and precise delivery. Journalists can now report news directly from the scene with greater ease, thanks to technological advancements. This transformation is pervasive, with digitalisation impacting every stage of the news process. Throughout history, humans have used various devices to create and share news. Nowadays, automated news production by nonhuman entities using algorithms is becoming increasingly important (Zamith & Westlund, 2022). From information gathering (Steiner, 2014), content production (Graefe, 2016), and distribution and consumption modalities (Wheatley & Ferrer-Conill, 2020) to the engagement of the interconnected audience, every aspect has transformed, including the journalistic profession itself (Zamith & Westlund, 2022). Consequently, these technological changes have also influenced journalistic practices within newsrooms and the profiles of their professionals (García & Vázquez, 2016). Within the domain of journalism, it is evident that the emergence of recent technologies necessitates professional recalibration, entailing the assimilation of innovative methodologies and tools, as well as the acquisition of technical proficiencies (López-García et al., 2017).